2020
DOI: 10.2147/ijgm.s277947
|View full text |Cite
|
Sign up to set email alerts
|

<p>Molecular Characterization and Disease-Related Morbidities of β-Thalassemia Patients from the Northeastern Part of Iraq</p>

Abstract: Background β-thalassemia is a significant problem in the northeastern part of Iraq, and has imposed a huge burden on the health authorities. Objective To identify the molecular characterization and morbidity prevalence in transfusion-dependent thalassemia (TDT) and non-transfusion dependent thalassemia (NTDT) phenotypes in northeastern Iraq. Patients and Methods This is a cross-sectional study conducted on 242 β-thalassemia patients from 162 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…A study conducted in 2020 expressed 54.5% was on regular blood transfusion. 15 We found another study held in 2017which showed that 62% of the study population was TDT (transfusion dependent thalassaemia) and rest of the study population was NTDT(non-transfusion dependent thalassaemia). 17 A study held in 2020 showed that 56.73% of the study population requires regular blood transfusion which is consistent with our study too.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A study conducted in 2020 expressed 54.5% was on regular blood transfusion. 15 We found another study held in 2017which showed that 62% of the study population was TDT (transfusion dependent thalassaemia) and rest of the study population was NTDT(non-transfusion dependent thalassaemia). 17 A study held in 2020 showed that 56.73% of the study population requires regular blood transfusion which is consistent with our study too.…”
Section: Discussionmentioning
confidence: 87%
“…4 Another study conducted 2020 expressed 53.3% was male. 15 Again, a study conducted in 2013 showed that 53% of the study population was male and 47% was female. 16 So, all of these studies results are consistent with our study.…”
Section: Discussionmentioning
confidence: 98%
“…Beta thalassemia is defined as a group of recessive genetic disorders of hemoglobin synthesis that caused health disorders of prominent importance in the tropical part, especially in low-resource countries, as it is in Iraq [1 ]The annual total rate of symptomatic persons is estimated to be about 1 in 100,000 cases worldwide. Three types of thalassemia have been described: thalassemia major, thalassemia intermediate and thalassemia minor.…”
Section: Introductionmentioning
confidence: 99%